PENGARUH RETURN ON EQUITY TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR FARMASI PERIODE 2016-2020 - Ulfi Jefri; Sita Nurhasanah; Rika Kartika (JURNAL ILMIAH EDUNOMIKA, 2022)
The manufacturing industry is an industry that excels compared to other sectors, despite the pressure from the coronavirus outbreak. conventional medicine, pharmacy with a growth percentage of 5.59 percent. This study has the aim of understanding the partial relationship of X with Y and Z moderating X against Y in the Pharmacy sub-sector manufacturing industry listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The research method used is descriptive quantitative, and the population used is the entire manufacturing industry focused on the pharmaceutical sub-sector with a total of 10 companies and a sample of 7 companies, the observation period is 2016-2020. The results showed that the tcount of the Return On Equity (ROE) variable on Firm Value (X versus Y) using SPSS showed tcount > ttable (5.278 > 2.035) and showed sig results of (0.000 < 0.05). And Corporate Social Responsibility (CSR) which is used for the moderating variable, the results of the MRA test are obtained showing the results of sig 0.011